THE DEVELOPMENT OF PORONG ESTUARY - Undang Hernawan (Marine Geological Institute of Indonesia, 2008)
Coastal zone is an area of interaction between the land and the sea. Coastal dynamic is influenced by many factors, such as sedimentation and current. Development of an area in the coastal zone such as estuary is also influenced by suck factors. Development of porong estuary is analyzed by interpretation of Image data, i.e. Landsat TM data that acquired in July, 29th 1975, August, 17th 1994, August, 17th 2000, May, 19th 2002 and Quickbird imagery that acquired in April, 25th 2008. Field survey has been done on April 2008. Based on data interpretation, there are accretion and abrasion in this area. The accretion in the southern part of Porong estuary between 1975 – 2008 is about 33.15 km or about 3.15 km/year equivalent to 1,492.29 Ha. The abrasion area in the northern part of Porong estuary in 33 years since 1975 till 2008 is around 0.5 km or aproximately 15.15 m/year equivalent to 222.45 Ha of wide or 6.802 Ha/year. Development of Porong delta, especially in the southern part of Porong estuary, is caused by change of pattern and main stream of Porong River from the noth to the south. This river delivered large volume of sediments and precipated at this area without or minor influence from the sea. Porong delta is a fluvial delta. Coastal characteristic is mangrove, muddy sediment and locally is sand sediment. Land use in this area is fish pond and mangrove. Key words: Porong estuary, Satellite imagery Pantai/pesisir merupakan wilayah antara daratan dan lautan yang masih dipengaruhi oleh keduanya. Dinamika pantai akan dipengaruhi oleh faktor-faktor dari daratan seperti sedimentasi dan faktor dari lautan seperti arus. Demikian halnya perkembangan suatu daerah di pesisir, seperti daerah muara, dipengaruhi oleh daratan dan lautan. Perkembangan muara Porong dianalisis berdasarkan interpretasi citra satelit, yaitu Landsat hasil perekaman 29 Juli 1975, 17 Agustus 1994, 17 Agustus 2004, 19 Mei 2002 dan citra Quickbird perekaman 25 April 2008. Survey lapangan dilaksanakan pada bulan April 2008. Berdasarkan interpretasi citra, ditemukan daerah akresi dan abrasi pada daerah penelitian. Daerah akresi ditemukan di bagian selatan daerah penelitian yaitu sekitar 33.15 km selama 1975–2008 atau sekitar 3.15 km/tahun dengan luasan sekitar 1,492.29 Ha. Daerah abrasi umumnya terdapat di muara Kali Porong sebelah utara, yaitu sejauh 0.5 km selama 33 tahun atau kira-kira 15.15 m/tahun dengan luasan 222.45 Ha atau sekitar 6.802 Ha/tahun. Perkembangan muara dan delta Porong, terutama di muara sebelah selatan, diperkirakan karena adanya perubahan arah utama Sungai Porong, yang berubah dari arah utara kea rah selatan. Aliran sungai ini membawa banyak sedimen dan diendapkan pada daerah ini, karena tiada atau kurangnya pengaruh dari laut. Delta Porong termasuk kawasan delta fluvial. Karakteristik daerah pantai umumnya berlumpur dengan setempat berupa pasir. Penggunaan lahan pada daerah ini umumnya berupa tambak dan mangrove. Kata Kunci : Delta Porong, citra Satelit